Afghanistan : Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Joint Staff Advisory Note discusses Afghanistan's Poverty Reduction Strategy Paper's annual progress report. Afghanistan has experienced a number of extraordinary challenges that delayed its implementation. The security situation deteriorated markedly and has been dominated by the cross-border Taliban insurgency. Growth started to recover from a devastating drought. In May 2008, food and fuel prices peaked, leading to high inflation and pressure on the budget for additional fuel and food subsidies. These threats to macroeconomic stability have been accompanied by a period of political uncertainty for Afghanistan's leadership.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet